Circular economy disclaimers: Rethinking property relations at the end of cheap nature - Isenhour, Cindy; Berry, Brieanne; Victor, Erin (Frontiers in Sustainability, 2023)
Converging environmental crises have inspired a movement to shift the dominant economic form away from a linear “take-make-waste” model and toward more circular forms that reimagine discarded materials as valuable resources. With the coming “end of cheap nature” (Moore, 2015), this invitation to reimagine value as something more than “the political other of capitalist value” (Gidwani and Reddy, 2011) is seen as both an environmental necessity and an opportunity for green growth. Less often discussed is that the circular economy, in its reconfiguration of value, (Schindler and Demaria, 2020) also has the potential to reshape contemporary property relations (Hobson, 2020) and dismantle existent forms of circularity. In this paper, we explore shifts in property relations through an analysis of three strategies often imagined as key to facilitating the transition to circularity —extended producer responsibility, product service systems, and online resale. Each case synthesizes existing research, public discourse, and our findings from a series of focus groups and interviews with circular economy professionals. The cases suggest caution given the possibility that some circular economy strategies can concentrate value and control of existing materials stocks, dispossess those most vulnerable, and alienate participants in existent reuse, recycling, and repair markets. Drawing on and adapting Luxemburg’s concept of primitive accumulation, Tsing’s ideas about salvage accumulation, Moore’s work on commodity frontiers and recent research on commoning (Gibson-Graham et al., 2016; Nightingale, 2019), we argue that without careful attention to relations of power, politics, and justice in conceptualizations of both ownership and the collective actions necessary to transform our economic forms in common, transitions toward the circular economy have the potential to exacerbate inequality.